2007
DOI: 10.1038/sj.onc.1210839
|View full text |Cite
|
Sign up to set email alerts
|

MTA1-mediated transcriptional repression of BRCA1 tumor suppressor gene

Abstract: Metastasis-associated tumor antigen 1 (MTA1), a component of the nucleosome remodeling and deacetylating (NuRD) complex is routinely upregulated in several cancers. In the present study, we investigated the potential role of MTA1 in BRCA1 transcriptional repression and subsequent chromosomal instability. MTA1-NuRD complex was found to negatively regulate BRCA1 transcription by physically associating with an atypical estrogen-responsive element (ERE) on the BRCA1 promoter. Moreover, MTA1 and HDAC complex recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
55
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 35 publications
1
55
0
Order By: Relevance
“…In this context, the studies presented here provide a mechanistic basis for the contribution of MTA1 in positively modulating HMMR expression, leading to cell invasion. As MTA1 regulates its target genes by acting either as a transcriptional corepressor or coactivator (21)(22)(23)(24), our results show that HMMR is a target of MTA1 and that MTA1 enhances HMMR expression at the transcriptional level by directly interacting with the HMMR promoter as a part of the pol II⅐c-Jun complex. In support of this, we have also observed a strong meta-analysis correlation between MTA1 and HMMR in the tissue samples of both breast cancer and prostate cancer patients.…”
Section: Mta1 Expression Correlates With Levels Of Hmmr-amentioning
confidence: 81%
See 1 more Smart Citation
“…In this context, the studies presented here provide a mechanistic basis for the contribution of MTA1 in positively modulating HMMR expression, leading to cell invasion. As MTA1 regulates its target genes by acting either as a transcriptional corepressor or coactivator (21)(22)(23)(24), our results show that HMMR is a target of MTA1 and that MTA1 enhances HMMR expression at the transcriptional level by directly interacting with the HMMR promoter as a part of the pol II⅐c-Jun complex. In support of this, we have also observed a strong meta-analysis correlation between MTA1 and HMMR in the tissue samples of both breast cancer and prostate cancer patients.…”
Section: Mta1 Expression Correlates With Levels Of Hmmr-amentioning
confidence: 81%
“…MTA1 (metastatic tumor antigen 1), a founding member of the MTA family of chromatin modifiers, forms an integral part of the NuRD (nucleosome remodeling and histone deacylation) complex, which is involved in transcriptional regulation, histone deacetylation, and chromatin remodeling. MTA1 executes its function on the target gene by recruiting either RNA polymerase II (pol II) or histone deacetylase to the target gene chromatin (21)(22)(23)(24). MTA1 is up-regulated in human cancers and also acts as an oncogene (25)(26)(27).…”
mentioning
confidence: 99%
“…Our laboratory, along with others, has shown that MTA1 associates with class I HDACs-HDAC1 and HDAC2 (28,32,33). However, MTA1 association with class II HDACs has not, as of yet, been documented.…”
Section: Mta1 Expression Inversely Correlates With Pten Expresmentioning
confidence: 99%
“…Earlier studies have demonstrated that MTA1 forms a corepressor complex with HDAC1/2 and is recruited to the target gene promoters, thereby repressing gene transcription (29). For example, the MTA1⅐HDAC2 complex was identified as a transcriptional corepressor of number of tumor suppressor genes such as BRAC1, p21WAF1, and RNF144, where the MTA1⅐HDAC2 complex recruits onto their promoters and down-regulates the expression of these genes, leading to accelerated tumor growth and metastasis (32,41,42). In this study, we identified MTA1 as a transcriptional corepressor of the tumor suppressor gene PTEN, but contrary to earlier studies, for the first time, we found that MTA1 but not MTA2 associates with class II HDAC4s and identified the first target of the MTA1⅐HDAC4 containing the NuRD complex, the PTEN.…”
Section: Mta1 Expression Inversely Correlates With Pten Expresmentioning
confidence: 99%
“…MTA1, the founding member of the MTA family, is widely up-regulated in human cancers and involved in tumorigenesis, tumor invasion, and metastasis (3,4). MTA1 not only functions as a transcriptional repressor of its targets, such as estrogen receptor-␣ (5) and breast cancer type 1 susceptibility protein (BRCA1) (6), but also as a transcriptional activator via interacting with RNA polymerase II on the breast cancer-amplified sequence 3 (BCAS3) (7) and paired box gene 5 (Pax 5) (8) promoters. In addition to the well recognized role of MTA1 in tumorigenesis and tumor progression, emerging data suggest that MTA1 is a DNA-damage responsive protein as the intracellular levels of MTA1 are induced by ionizing radiation (IR), and plays an important role in DNA double strand break repair (9).…”
mentioning
confidence: 99%